An illustration of review on Morphology and Medicinal aspects of Mushroom Cultivated worldwide - Babita Kumari; Sangeeta Pal; Hitesh Solanki (International Journal of Fungi, 2024)
Mushrooms are accepted as a superfood that provides a high content of nutrients. It offers many health benefits. Mushrooms can be enjoyed at various times but including them as part of a balanced meal in our daily routine. The consumption of mushrooms is becoming popular day by day as an unbalanced diet of people in developing countries. Fresh mushrooms, reported to have a high water content, are an effective way to both prolong their shelf life. They preserve their flavor and nutrients for a long day. In India, Bihar, Punjab, Himachal Pradesh, Rajasthan, Haryana, Uttar Pradesh, and Jammu & Kashmir are the major producing states with 90% of production. Button mushrooms are grown in temperate regions of India. Button, oyster, sap, and rice grass mushrooms are grown in tropical and subtropical climates. Under controlled conditions, button mushroom plants can be harvested 2–3 times a year, while seasonal mushrooms are harvested once a year. There is now an increased demand for mushrooms in the market. Additionally, out of different types of mushrooms, button mushrooms are highly grown in small fields, which boosts their popularity. They are a staple diet of health-conscious people all over the world. Mushrooms are the subsequent production throughout the world. Scientists reported approximately 7,000 different species, of which 1300 species seem to be edible. The entrepreneur always tries to promote his profits through innovation. Innovation links to solve the problem by using capabilities. The rising demand for mushrooms popularity among vegetarians is increasing day by day. However, now a day the minimum cost of Indian mushrooms in the international market seems to be more attractive to consumers. The objective of this review is to assess the demand for mushrooms in the global market. It’s a delicious, medicinal, and nutritionally healthy concept.
Keywords: Health; Mushroom; Nutrition; medicinal properties; mushroom commercialization